N‐Acyloxyphthalimide as Multitasking Directing Group for Sequential C‐H Functionalization. Issue 7 (15th February 2019) - Sun, Huan; Jiang, Yue; Chen, Xiao‐Wei; Zhou, Yi−Bo; Feng, Tao; Huang, Rong; Zheng, Yongsheng; Li, Zheng‐Hui; Liu, Ji‐Kai
Abstract: N ‐Acyloxyphthalimide has been demonstrated as a multitasking directing group considering its easy accessibility, multiple reactive sites, and multifarious transformations available to generate valuable structural diversified scaffolds. Polysubstituted heterocycles, such as isocoumarin, isoquinolone, and its second annulation products, could be obtained from N ‐acyloxyphthalimide and alkynes through a one‐pot reaction in the presence of nucleophilic reagents. Additionally, the ester group possessed on the resulting heterocycles could serve as a new building block to direct further functionalization. Abstract : N ‐Acyloxyphthalimide has been demonstrated as a multitasking directing group to obtain polysubstituted heterocycles, such as isocoumarin, isoquinolone, and its second annulation products through a one‐pot reaction in the presence of nucleophilic reagents. Additionally, the ester group possessed on the resulting heterocycles could serve as a new building block to direct further functionalization. We hope that this chemistry can offer a plausible strategy for rapidly increase molecular complexity and diversity.